Crisis and the Reproduction of Core-Periphery Relations on the Hungarian Housing Market - Pósfai, Zsuzsanna; Nagy, Gábor (European Spatial Research and Policy, 2018)
Housing markets can be understood as indicators of the spatial pattern of capital investment under contemporary financial capitalism. We take this point of entry in order to analyze core-periphery relations around the turning point of the global financial crisis of 2007–2008 on the Hungarian housing market. The instance of crisis sheds light on patterns of homogenization and differentiation; the effects of which can be understood by exploring housing market activity on various scales from the European to the local/regional. We argue that these two patterns of uneven development are inextricably linked and result in deepening sociospatial polarization.